Development of Metal and Machinery Small and Medium Enterprises (SMEs) in West Lombok Regency with the Blue Ocean Strategy Approach - Muhammad Zainuddin; Sudarmiatin; Agus Hermawan (Study Program Ekonomi Syari'ah, Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2022)
Blue Ocean Strategy aims to open new market share to minimize competition with similar competitors. After receiving a touch from the West Lombok Regency Industry and Trade Service (Prindag Lobar), the Metal and Machinery Community Activity Unit in West Lombok initially produced gates, trellises and other similar works, creating quite a lot of competition. So that with the guidance of the Service which offers solutions with the Blue Ocean Strategy, the metal and machine industry (SMEs) in West Lombok Regency can compete. This study used a qualitative method, data obtained from in-depth interviews with section heads of the metal, machine, electronics and transportation equipment (ILMEA) industry, descriptive analysis and source triangulation. This article reveals that Blue Ocean Strategy manufactures metal products and machinery in different segments. The Blue Ocean Strategy segment is offered in the form of changing the mindset and technical skills of metal and machining (SME) players. Metal and machinery SMEs are trained to manufacture machine products needed by the food and beverage industry. One of the concrete steps is the manufacture of machines for making palm sugar machines, coffee roasting machines and other processing machines. This has an impact on the shift of the metal and machine SME segment from household products to processed machine products.